Oxidative Stress in Age-Related Neurodegenerative Diseases: An Overview of Recent Tools and Findings - Dimitris Korovesis; Teresa Rubio-Tomás; Nektarios Tavernarakis (MDPI AG, 2023)
Reactive oxygen species (ROS) have been described to induce a broad range of redox-dependent signaling reactions in physiological conditions. Nevertheless, an excessive accumulation of ROS leads to oxidative stress, which was traditionally considered as detrimental for cells and organisms, due to the oxidative damage they cause to biomolecules. During ageing, elevated ROS levels result in the accumulation of damaged proteins, which may exhibit altered enzymatic function or physical properties (e.g., aggregation propensity). Emerging evidence also highlights the relationship between oxidative stress and age-related pathologies, such as protein misfolding-based neurodegenerative diseases (e.g., Parkinson's (PD), Alzheimer's (AD) and Huntington's (HD) diseases). In this review we aim to introduce the role of oxidative stress in physiology and pathology and then focus on the state-of-the-art techniques available to detect and quantify ROS and oxidized proteins in live cells and in vivo, providing a guide to those aiming to characterize the role of oxidative stress in ageing and neurodegenerative diseases. Lastly, we discuss recently published data on the role of oxidative stress in neurological disorders.